1984
DOI: 10.1037/0022-3514.46.3.621
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory hierarchical factor analyses of psychological distress measures.

Abstract: Previous factor-analytic research examining the dimensionality of psychological distress and depression has generally minimized the importance of the interrelationships existing among primary components of depression and distress. Restricted hierarchical factor-analysis models that simultaneously test for the presence and necessity of both primary and second-order factors are developed for the Beck Depression Inventory and the Psychiatric Epidemiology Research Interview. Similarities in the latent structure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
147
0
4

Year Published

1996
1996
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(163 citation statements)
references
References 43 publications
8
147
0
4
Order By: Relevance
“…Previous research with psychological constructs in general (e.g., Jöreskog, 1982;Newcomb & Bentler, 1988;Tanaka & Huba, 1984), and with measuring instruments in particular (Byrne, 1988(Byrne, , 2001, has demonstrated that the specification of correlated errors can often lead to substantially better fitting models. Bentler and Chou (1987) also argue that the specification of a model that forces these error parameters to be uncorrelated is rarely appropriate with real data.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research with psychological constructs in general (e.g., Jöreskog, 1982;Newcomb & Bentler, 1988;Tanaka & Huba, 1984), and with measuring instruments in particular (Byrne, 1988(Byrne, , 2001, has demonstrated that the specification of correlated errors can often lead to substantially better fitting models. Bentler and Chou (1987) also argue that the specification of a model that forces these error parameters to be uncorrelated is rarely appropriate with real data.…”
Section: Discussionmentioning
confidence: 99%
“…According to Kline (2016), the minimum set of fit statistics to be reported in terms of this analysis are the model chi-square (χ 2 ), degrees of freedom (df), p-value, Root Mean Square Error of Approximation (RMSEA) (Steiger, 1990), Comparative Fit Index (CFI) (Bentler, 1990), and Standardized Root Mean Square Residual (SRMR) (Bentler, 1995). In light of this, the recommended values as well as the Goodness of Fit Index (GFI) (Jöreskog & Sörbom, 1989;Tanaka & Huba, 1984), Adjusted Goodness of Fit Index (AGFI) (Jöreskog & Sörbom, 1989), Normed Fit Index (NFI) (Bentler & Bonnet, 1980), and Non-Formed Fit Index (NNFI) (Bentler & Bonnet, 1980) values were used to assess model fit. The normed chi-square (χ 2 /df) was not used, as Kline (2016) proposed it to have a limited statistical or rational foundation and no part in fit testing.…”
Section: Findings Of the Exploratory Factor Analysismentioning
confidence: 99%
“…According to Tanaka and Huba (1984), a high correlation of the first-order factors to second-order factors may be indicative of valid higher order relationship between them. From Figure 2, it is seen that the first-order factors correlate and are significantly different from zero, confirming their proposed second-order factor structure.…”
Section: Analysis Of Second-order Formative Constructsmentioning
confidence: 99%